Exuberant long noncoding RNA expression may sculpt Igh locus topology - Drake, Ellen B.; Naiyer, Sarah; Qu, Xinyan; Bhat, Khalid; Farooq, Hammad; Maienschein-Cline, Mark; Liang, Jie; Kenter, Amy L. (Frontiers in Immunology, 2025)
Diverse Igh repertoires require successful V(D)J recombination allowing B cell receptor expression and Ig secretion for humoral immune responses. Igh locus contraction has been implicated in generating spatial proximity between distal VH segments and the recombination center via cohesin mediated loop extrusion. However, it remains unclear why some distal VH segments recombine with high frequency while other more proximal VH are rarely used. Long non-coding RNAs (lncRNAs) have emerged as regulators of cellular development, differentiation and gene expression. Here we report exceptionally high expression of lncRNAs at the Igh locus and other AgR loci engaged in V(D)J recombination. A tight correlation was found between positions of multi-exonic lncRNAs, Igh enhancers and chromatin loop anchors. We propose an integrated model of factors including lncRNAs and loop extrusion in determining Igh locus topology and VH gene usage during recombination.